IMAGE-BASED VIRTUAL TOURS AND 3D MODELING OF PAST AND CURRENT AGES FOR THE ENHANCEMENT OF ARCHAEOLOGICAL PARKS: THE VISUALVERSILIA 3D PROJECT - C. Castagnetti; M. Giannini; R. Rivola (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2017)
The research project VisualVersilia 3D aims at offering a new way to promote the territory and its heritage by matching the traditional reading of the document and the potential use of modern communication technologies for the cultural tourism. Recently, the research on the use of new technologies applied to cultural heritage have turned their attention mainly to technologies to reconstruct and narrate the complexity of the territory and its heritage, including 3D scanning, 3D printing and augmented reality. Some museums and archaeological sites already exploit the potential of digital tools to preserve and spread their heritage but interactive services involving tourists in an immersive and more modern experience are still rare. The innovation of the project consists in the development of a methodology for documenting current and past historical ages and integrating their 3D visualizations with rendering capable of returning an immersive virtual reality for a successful enhancement of the heritage. The project implements the methodology in the archaeological complex of Massaciuccoli, one of the best preserved roman site of the Versilia Area (Tuscany, Italy). The activities of the project briefly consist in developing: 1. the virtual tour of the site in its current configuration on the basis of spherical images then enhanced by texts, graphics and audio guides in order to enable both an immersive and remote tourist experience; 2. 3D reconstruction of the evidences and buildings in their current condition for documentation and conservation purposes on the basis of a complete metric survey carried out through laser scanning; 3. 3D virtual reconstructions through the main historical periods on the basis of historical investigation and the analysis of data acquired.